Preventing delayed cracks in SUS304 deep drawn cups using extreme blank holding forces aided by nanolubrication - Tan, Chin Joo; Ibrahim, Muhammad Shafiq; Muhamad, Mohd Ridha (Springer Verlag, 2019)
Disappearance and reappearance of delayed cracks were observed in deep drawing process of SUS304 cylindrical cups under elevated blank holding forces (BHF) of 8~32 kN with nanolubricants containing 1~3 wt% SiO 2 concentrations at limiting draw ratio. The widest crack-free BHF range determined experimentally, i.e., 29~31 kN was for 2 wt% SiO 2 . Delayed cracks were observed below and beyond this BHF range. The frictional force at the flange surfaces slightly increased when entering the crack-free BHF range, as evidenced by the rebound in sidewall thickness, relative intensity of α′-martensite, elongated height, and drawing force beyond 28 kN. The coefficients of friction for each BHF were obtained with finite element simulations. Since residual stresses developed along the outer surface of the cup due to the unbending of the material when the material left the draw die profile, the slight increase in frictional force in the radial direction along the flange surfaces reduced the circumferential tensile residual stress of the cup, particularly at 80% cup height. The elimination of delayed cracks was attributed to the lower tensile residual stress gradient, i.e., lower and higher tensile residual stresses at 80% and 100% cup heights, respectively. However, the excessive increase at 100% cup height was a result of the increase in longitudinal compressive stress at BHF beyond 31 kN due to the stress equilibrium, leading to the reappearance of cracks. The minimum BHF required to eliminate cracks changed minimally with increasing SiO 2 concentration. © 2018, Springer-Verlag London Ltd., part of Springer Nature.